PENGARUH BRAND IMAGETERHADAP KEPUTUSAN PEMBELIAN PRODUK AYAM GORENG RUMAH MAKAN LEZZAT KUTOARJO (STIE Rajawali Purworejo, 2018)
The purpose of this study is to determine the effect of brand image with purchase decisions at Restaurant Lezzat Kutoarjo. Sampling technique in this research use Accidental Sampling. Since the population is large and the number is unknown and can not be measured with certainty, then the sample used is 100 people. Data analysis techniques used are simple regression, coefficient of determination,and t test. Based on the research that the authors do ultimately obtained the regression equation of the effect of brand image on the purchase decision as follows: Y = 5.163 + 0.646X. This means that, if the value of the brand image variable in the research object is equal to zero, then the level or amount of decision variable purchasing fried chicken products Leete 5.163. The amount of change of decision variable of purchase of fried chicken product of Lezzat Restaurant is 0,545, this means purchasing decision of 54,5% influenced by brand image variable, while 45,5% influenced by other variable not examined, such as price, strategic location, life, role and social status, and so on. The hypothesis produces a positive and significant influence between the brand image and the purchase decision.